2009
DOI: 10.1186/1756-9966-28-120
|View full text |Cite
|
Sign up to set email alerts
|

Serum human chorionic gonadotropin is associated with angiogenesis in germ cell testicular tumors

Abstract: Background: Germ cell testicular tumors have survival rate that diminishes with high tumor marker levels, such as human chorionic gonadotropin (hCG). hCG may regulate vascular neoformation through vascular endothelial growth factor (VEGF). Our purpose was to determine the relationship between hCG serum levels, angiogenesis, and VEGF expression in germ cell testicular tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Human chorionic gonadotropin (hCG) is a hormone involved in the angiogenic process in normal tissues, such as the placenta (Zygmunt et al. , 2002), but it has been recently found to participate in TGCT neovascularization (Arrieta et al. , 2009).…”
Section: Vascularization Of Spontaneous Tgctsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human chorionic gonadotropin (hCG) is a hormone involved in the angiogenic process in normal tissues, such as the placenta (Zygmunt et al. , 2002), but it has been recently found to participate in TGCT neovascularization (Arrieta et al. , 2009).…”
Section: Vascularization Of Spontaneous Tgctsmentioning
confidence: 99%
“…as the placenta (Zygmunt et al, 2002), but it has been recently found to participate in TGCT neovascularization (Arrieta et al, 2009). This finding suggests that hCG may represent a promising molecular target in TGCT treatment.…”
Section: Vascularization Of Spontaneous Tgctsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCG, especially the beta subunit of HCG, is produced by NGGCTs that consist of pure or mixed embryonal carcinoma or choriocarcinoma. These tumor markers have clear roles in the diagnosis, staging, risk classification, and clinical management of testicular germ cell tumors [13][14][15]. The SIOP CNS-GCT-96 (International Society of Paediatric Oncology Central Nervous System-Germ Cell Tumor-1996) protocol reported AFP [ 1000 ng/ml at diagnosis and/or residual disease after treatment were risk factors for relapse of NGGCTs [16], but the relationship between serum tumor marker concentration and prognosis remains unclear in patients with intracranial germ cell tumor.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that owing to biological similarity to LH, tumor-secreted hCG/β-hCG can cause precocious puberty by stimulating Leydig cells [81,82]. On the other hand, increased concentrations of hCG have been shown to be associated with tumor angiogenesis, which might explain its link to poor prognosis [83].…”
Section: β-Hcgmentioning
confidence: 99%